Contribution of Bronchoscopic Examination in Diagnosis of Congenital Tracheo-Broncho-Pulmonary Malformations - Antigona Trofor; Ramona Miron; Letitia Trofor; Mihaela Ciobanu (Romanian Society of Oral Rehabilitation, 2010)
Diagnosis of congenital malformations of the trachea, bronchi and lung is often a stumbling block, even for experienced clinicians, given the rarity of some anomalies, many clinical masks and the complexity of investigational methods required to confirm such conditions. In current practice of an adult respiratory medicine service, in the congenital lung pathology, most often, physicians can meet cases of: pulmonary hypoplasia, intralobar pulmonary sequestration, tracheal strictures, abnormal division of the airways, air cysts, and rarely congenital lobar emphysema and pulmonary agenesis. Many of these malformations are discovered in newborn or infant, because of pulmonary and cardiovascular complications and frequent combination with other congenital anomalies. So, these anomalies should be included in differential diagnosis of lung or mediastinal disease, especially in young adult. No doubt, bronchoscopy is one of the basic tracks in the diagnosis of these malformations. Some are correctable if promptly recognized, others are incompatible with life, while probably the majority are symptomless, appearing as incidental findings at routine medical, surgical or post-mortem examination. Non-recognition of this lung disease group in current medical practice can lead to serious diagnostic errors. Basic concepts are presented in diagnosis of major malformations of trachea, bronchi and lung encountered in current medical practice and some examples of bronchoscopic aspects as experienced in several respiratory medicine services are given.